Congenital midline labial sinus of the upper lip - Anka Sharma; Subhash P Kumbhare; Ashita Kalaskar (Wolters Kluwer Medknow Publications, 2019)
Congenital midline labial sinus is a rare condition affecting both the upper and lower lips. This anomaly has been reported in either gender but with a slightly increased predilection in females. It is known to occur either in isolation or in association with other congenital malformations such as cleft lip, cleft palate, van der Woude syndrome, median lip pit, brachidactilia, tongue tie, hypertelorism, notch of median vermillion border, nasal fistula, and abnormal hair pattern. In this article, we report a case of congenital midline sinus (without any associated congenital malformation) affecting the upper lip in a 12-year-old Indian male. Furthermore, a review of literature has been attempted on this condition.